2011
DOI: 10.1038/nmat3082
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of a sulphur-terminated graphene nanoribbon within a single-walled carbon nanotube

Abstract: The ability to tune the properties of graphene nanoribbons (GNRs) through modification of the nanoribbon's width and edge structure widens the potential applications of graphene in electronic devices. Although assembly of GNRs has been recently possible, current methods suffer from limited control of their atomic structure, or require the careful organization of precursors on atomically flat surfaces under ultra-high vacuum conditions. Here we demonstrate that a GNR can self-assemble from a random mixture of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
265
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(279 citation statements)
references
References 33 publications
9
265
1
4
Order By: Relevance
“…Contrary to previously reported irreversible beam-induced dynamics [12][13][14][15][16][17][18][19][20][21][22] , here we report a beaminduced reversible conformational transformation of the trapped Si 6 cluster in a graphene nanopore. Density-functional calculations of an embedded Si 6 cluster are used to probe its bonding to the host graphene lattice and the energy barriers for the conformational transformation.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previously reported irreversible beam-induced dynamics [12][13][14][15][16][17][18][19][20][21][22] , here we report a beaminduced reversible conformational transformation of the trapped Si 6 cluster in a graphene nanopore. Density-functional calculations of an embedded Si 6 cluster are used to probe its bonding to the host graphene lattice and the energy barriers for the conformational transformation.…”
contrasting
confidence: 99%
“…Figure 1 shows a sequential set of annular dark field (ADF) Z-contrast images of a single Si 6 cluster trapped in a graphene nanopore. Electron-beam-induced ejection of carbon atoms and defect creation/migration has been actively studied in graphene and carbon nanotubes [12][13][14][15][16][17][18][19][20][21][22] . Contrary to these irreversible dynamics, we find that an oscillatory motion occurs in the trapped Si 6 cluster: one of the Si atoms executes a back-and-forth motion corresponding to the reversible conformational change of the Si 6 cluster in the graphene pore.…”
mentioning
confidence: 99%
“…This demonstrates a remarkable property of carbon nanotubes to act not only as nanoreactors constraining the space around the chemical reaction and templating the formation of nanoclusters or the growth of nanoribbons, but also as electrically active host-structures lending their electrons when they are required for a chemical reaction to occur inside SWNT, and retrieving electrons back when they are no longer required by the guest-species. In summary, carbon nanotubes are becoming an increasingly important class of nanoscale containers and reactors, where the pathways of chemical reactions can change significantly as a result of the restricted space of the reaction [5][6][7][8][9][10][11][12][13][14][15][16][17], or due to the interactions between the reactant molecules or catalyst particles with the host-nanotube [23,24]. Being highly conducting and having a symmetric distribution of filled and empty electronic states, SWNT possess remarkable electric properties and a unique ability to donate or accept electrons, which make nanotubes distinct among other nanocontainers and nanoreactors.…”
Section: Equationmentioning
confidence: 99%
“…44,47 It was found that mean-field Hubbard treatment of Coulomb interactions gives a minimal spin polarization and an associated magnetic domain wall, 42,43 whereas density functional calculations predict finite total magnetization. 44,47 On the experimental side, although we are not aware of Möbius graphene nanoribbons with zigzag edges yet, twisted nanoribbons were recently obtained inside carbon nanotubes through electron irradiation of functionalized fullerenes 36 and a stable Möbius aromatic hydrocarbon was synthesized by Ajami et al 41 In this work we describe the effect of Möbius topology on the one-electron properties of graphene nanoribbon rings as a function of the number of carbon chains, both even and odd. We compare the Möbius topological insulator with normal insulators, cylindrical graphene nanoribbon rings with cyclic boundary conditions.…”
Section: Introductionmentioning
confidence: 96%